Application of the comet assay in erythrocytes of Oreochromis niloticus (Pisces): a methodological comparison - Christofoletti, Cintya A. [UNESP]; David, José Augusto O.; Fontanetti, Carmem S. [UNESP] (Sociedade Brasileira de Genética, 2009)
The present study applied the comet assay to erythrocytes of Oreochromis niloticus with the aim of improving protocols to detect DNA damage in these cells, by using two distinct pHs (pH = 12.1 and pH > 13) and evaluating whether there is a correspondence between silver and ethidium bromide staining. Comets were visually examined and, the frequency of cells with and without damage was obtained, as well as the distribution of classes and scores. By using the Kruskal-Wallis test, our results revealed that pH 12.1 is more effective, although both pHs can be used. Our findings also suggest that silver staining can substitute ethidium bromide, an expensive and highly toxic stain that requires specific equipment for examination.
Keywords: comet assay; ethidium bromide; silver staining; tilapia